Prognosis and cause of death in patients with left atrial appendage thrombus treated with or without anticoagulation therapy. (25th November 2020) - Kagawa, E; Kato, M; Oda, N; Kunita, E; Nagai, M; Yamane, A; Kobayashi, Y; Shiota, H; Osawa, A; Kobatake, H; Takeuchi, M; Dote, K
Abstract: Background: Thrombus in left atrial appendage (LAA) is associated with cardiogenic ischemic stroke; however, little is known about prognosis of patients with LAA thrombus detected by transoesophageal echocardiography (TOE). Purpose: This study is to investigate the prognosis of patients with LAA thrombus and their cause of death. Methods: Between 2005 and 2016, the patients who were performed TOE in our hospital were enrolled in this retrospective observational study. Five-year stroke free and survival curves were constructed by Kaplan-Meir method and cause of death were assessed. Results: Among the 1263 study patients, LAA thrombus was detected in 146 (12%) patients. The patients with LAA thrombus were elder (74 y [66–79 y] vs. 70 y [62–76 y], P<0.001), than those without LAA thrombus, respectively. The prevalence of male sex (67% vs. 69%, P=0.63) were similar between the 2 groups. The prevalence of CHA2DS2-VASc score ≥2, d-dimer (1.7 mcg/ml [0.9–3.5 mcg/ml] vs. 0.8 mcg/ml [0.5–2.2 mcg/ml], P<0.001), and plasma brain natriuretic peptide (315 pg/ml [128–515 pg/ml] vs. 126 pg/ml [47–284 pg/ml], P<0.001) were higher in the patients with LAA thrombus than those without (89% vs. 78%, P=0.003). The LAA velocity was slower in the patients with LAA thrombus than those without (23 cm/s [15–34 cm/s] vs. 51 cm/s [35–72 cm/s], P<0.001). The prevalence of receiving anticoagulation therapy before (34% vs. 24%, P=0.01) and after (98% vs. 66%, P<0.001) TOE 1 month were higher in the patients with LAA thrombus than those without. The 5-year stroke free rate was lower in the patients with LAA thrombus than those without (82% vs. 93%, P<0.001); however, the 5-year survival were similar between the 2 groups (84% vs. 84%, P=0.93) (Figure). The cause of death as ischemic stroke was only 7% (1/14) and 3% (3/94), (P=0.43); the cardiac cause (14% vs. 43%, P=0.07) and the malignancy (35% vs. 29%, P=0.75) were the frequent cause of death in the patient with LAA thrombus and those without, respectively. Conclusions: The patients who were detected thrombus in the LAA had higher incidence of ischemic stroke; however, the 5-y survival were similar. The ischemic stroke was not major cause of death in the patients with and without LAA thrombus. The higher rate of receiving anticoagulation therapy may be one of the causes of the discrepancy. Funding Acknowledgement: Type of funding source: None